Analysis of Mathematical Critical Thinking Skills using Problem-Based Learning Models in Junior High School Students - Aritonang, Paulani Sucahya Br; Hutajulu, Masta; Purwasih, Ratni ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2024)
The ability to think critically is currently one of the abilities that students need to have because with the ability to think critically in students can improve the quality of education in Indonesia, with this statement this research was conducted with the aim of describing the critical thinking skills of junior high school students using a problem-based learning model on quadratic equation material. This type of research is in the form of descriptive research with qualitative methods. This research was located at SMPN 3 Cimahi with 9 subjects who had high, medium and low abilities in critical thinking covering 3 classes. The data collection technique was carried out by providing 4 description questions and interviews to the subjects. Data analysis techniques in research refer to qualitative data analysis according to Miles and Huberman. The results of the study were measured based on indicators of critical thinking skills according to Facion (2015) where, 67% of students were able to interpret, 58% of students were able to analyze, 72% of students were able to evaluate, and 69% of students were able to infer so that it could be concluded that there was a significant influence of the problem-based learning model on critical thinking skills.